Trends in Project-Based Learning for Developing Critical Thinking Skills in Science Education: A Bibliometric Review - Zulkarnaen, Zulkarnaen; Rahayu, Satutik; Artayasa, I Putu (International Journal of Science Education and Science, 2025)
This study examines the role of Project-Based Learning (PjBL) in enhancing critical thinking skills in science education, focusing on research published from 2019 to 2024. The primary objective is to analyze trends in the literature related to PjBL and its impact on students' critical thinking, with an emphasis on integrating Science, Technology, Engineering, and Mathematics (STEM) education. A bibliometric approach was used, analyzing data from academic databases such as Scopus and Google Scholar, using tools like Publish or Perish 8 and VOSviewer. The results show a significant increase in publications on PjBL, particularly regarding critical thinking and STEM integration. Key themes such as problem-solving, collaboration, and the use of digital tools have gained prominence. The study also highlights the growing interest in technology-enhanced PjBL, especially in hybrid and online learning environments. PjBL is shown to effectively foster critical thinking by engaging students in real-world, inquiry-based projects. Future research should explore the role of digital tools in PjBL and its long-term impact on students' problem-solving abilities.